Simulation and comparison of progression-free survival among patients with non-squamous non-small-cell lung cancer receiving sequential therapy. Issue 1 (January 2014) - Walzer, Stefan; Chouaid, Christos; Lister, Johanna; Gultyaev, Dmitry; Vergnenegre, Alain; de Marinis, Filippo; Meng, Jie; de Castro Carpeno, Javier; Crott, Ralph; Kleman, Martin; Ngoh, Charles
<x xml:space="preserve">Abstract</x> Objectives: In recent years, the treatment landscape in advanced non-squamous non-small-cell lung cancer (nsNSCLC) has changed. New therapies (e.g., bevacizumab indicated in first line) have become available and other therapies (e.g., pemetrexed in first line and second line) moved into earlier lines in the treatment paradigm. While there has been an expansion of the available treatment options, it is still a key research question which therapy sequence results in the best survival outcomes for patients with nsNSCLC. Methods: A therapy-sequencing disease model that approximates treatment outcomes in up to five lines of treatment was developed for patients with nsNSCLC. The primary source of data for progression-free survival (PFS) and time to death was published pivotal trial data. All patients were treatment-naïve and in the PFS state, received first-line treatment with either bevacizumab-based therapy or doublet chemotherapy (including the option of pemetrexed + cisplatin). Patients would then progress to a subsequent line of therapy, remain in PFS or die. In case of progression, it was assumed that each survivor would receive a subsequent line of therapy, based on EMA licensed therapies. Weibull distribution curves were fitted to the data. Results: All bevacizumab-based first-line therapy sequences analyzed achieved total PFS of around 15 months. Bevacizumab + carboplatin + paclitaxel (first line) → pemetrexed (second line) → erlotinib (third line) → docetaxel (fourth line) resulted in total mean PFS time of 15.7 months, for instance. Sequences with pemetrexed in combination with cisplatin in first line achieved total PFS times between 12.6 and 12.8 months with a slightly higher total PFS time achieved when assuming pemetrexed continuation therapy in maintenance after pemetrexed + cisplatin in first-line induction. Overall survival results followed the same trend as PFS. Conclusion: The model suggests that treatment-sequencing strategies starting with a bevacizumab-based combination in first line yield better survival outcomes than those starting with pemetrexed-based combinations, a result that is attributable to the possibility of one further line of treatment with first-line bevacizumab-based treatment sequences.